Relationship between the plasma testosterone level and pain reaction times in male rats - Oyekunle, O.A.; Fibironke, G.; Ige, S.F.; Udoh, U.S.; Okojie, A.K. (Нейрофизиология, 2009)
Male prepubertal (about 4 weeks old) Wistar rats were used to estimate the pain reaction times using the tail-flick and hot-plate models; the testosterone concentration in all the animals before the tests in the blood plasma was measured. The same sets of animals were kept for the next 4 weeks under standard conditions; the experiment was repeated, and pain reaction times were also evaluated in the 8-week-old rats with blood samples collected to determine the plasma testosterone level. The results showed significant (P < 0.01) increases in the pain reaction times in both pain models in pubertal animals observed in a parallel manner with a corresponding significant (P < 0.01) increase in the plasma testosterone level. Therefore, age and sex are important factors in the choice of animals in pain experiments. У щурів-самців препубертатного віку (чотири тижні) вимірювали латентні періоди больових реакцій в умовах тестів «відсмикування хвоста» та «гарячої пластинки»; у всіх тварин перед тестами вимірювалася концентрація тестостерону в плазмі крові. Ці ж самі групи тварин утримувалися протягом чотирьох тижнів у стандартних умовах, після чого експеримент повторювали на восьмитижневих щурах (вимірювали час больових реакцій та рівень тестостерону). Для тварин, що досягли віку статевої зрілості, було характерне істотне (P < 0.01) збільшення латентних періодів больових реакцій в обох використаних моделях, що відбувалося паралельно з відповідним вірогідним (P < 0.01) збільшенням рівня тестостерону в плазмі. Отже, вік і стать є найважливішими факторами при відборі тварин для проведення експериментів з больовою стимуляцією.